Trehalose 6,6′-Dimycolate and Lipid in the Pathogenesis of Caseating Granulomas of Tuberculosis in Mice - Hunter, Robert L. (American Society for Investigative Pathology, 2006)
Trehalose 6,6′-dimycolate (TDM) is the most abundant, most granulomagenic, and most toxic lipid extractable from the surface of virulent Mycobacterium tuberculosis (MTB). We further examined its toxicity, which requires activation by oily surfaces. Injections of MTB and/or TDM into sensitized mice induced caseating granulomas that centered on oil droplets. If large doses of MTB were injected in saline, caseating granulomas developed in adipose tissue, but MTB with surface TDM removed induced only acute inflammation that did not persist. Variations in protocols produced several variants of caseating granulomas, each with characteristics of human tuberculosis. In each instance, MTB were localized in fat cells or oil drops during initiation of caseating granulomas suggesting that necrosis was caused by activation of the toxicity of TDM toxicity. Evidence extending these findings to the lung was derived from the observation that in sensitized mice, as in humans, tuberculosis development stimulates accumulation of lipid selectively in alveoli. MTB preferentially associated with lipid droplets in developing necrotic foci in late-stage murine tuberculosis. This supports the hypothesis that pulmonary tuberculosis sequesters MTB in a protected environment that accumulates lipid until it is able to activate the toxicity of TDM and initiate necrosis that results in caseating granulomas.